“Like a Certain Tornado of Peoples”: Warfare of the European Huns in the Light of Graeco-Latin Literary Tradition - Nikonorov, Valery P. (Anabasis. Studia Classica et Orientalia, 2010)
The paper deals with the art of warfare of the Huns, who invaded Southeast Europe in the last third of the 4th century A.D. and dominated there through the third quarter of the 5th century. It is described on the basis of all the available Greek and Latin written sources. Matters of the author’s consideration are arms and armour, horse equipment, armed forces, strategy and tactics, siegecraft and the structure of military organization. Some part of the paper contains critics of R. P. Lindner’s theory about the “dismounting” of the majority of Hun cavalry troops at least by the time of the great ruler Attila.